Fatigue state and external load effects on firefighter sprinting biomechanics - Mao, Chuangui; Wang, Ziwen; Zhang, Xinxin; Ma, Xiaoyi; Zeng, Sihang; Hao, Yunfei; Liu, Weiguo; Miao, Yu (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study investigates the biomechanical effects of fatigue and load on professional firefighters during sprinting, aiming to elucidate movement adaptations and injury risks under occupational rescue scenarios. We hypothesized that fatigue and load would independently impair sprinting performance and alter lower-limb biomechanics, leading to compensatory increases in joint moments and muscle activation.MethodsSixteen firefighters (23.13 ± 3.52 years) performed 20-m sprints carrying different loads (10–30 kg) in pre-/post-fatigue states. The statistical analysis was performed using SPSS and SPM1d for the two-way repeated-measures ANOVA.ResultsThere were significant differences in the gait speed (F = 14.019, p < 0.001, η2 = 0.683), step length (F = 30.512, p < 0.001, η2 = 0.685), stance time (F = 20.256, p < 0.001, η2 = 0.591), rectus abdominis (F = 6.757, p = 0.004, η2 = 0.326), and rectus femoris (F = 13.434, p = 0.002, η2 = 0.490) under different load tasks. The results of SPM1d revealed significant differences in the hip flexion/extension angles (F = 5.626, p = 0.049, 89.38%–99.30%), hip flexion/extension moments (F = 9.981, p < 0.001, 92.16%–100%), and ankle dorsiflexion/plantar flexion moments (F = 8.852, p = 0.003, 66.19%–78.98%) during the stance phase.ConclusionWhen sprinting with external weight constraints, gait metrics are negatively impacted, and compensating kinetic strategies increase push-off power from the hip and ankle of the dominant leg. These adaptations are further reflected in increased activation of the muscles around the hip joint of the firefighters.